1997
DOI: 10.1121/1.420077
|View full text |Cite
|
Sign up to set email alerts
|

Performance of noise indices in air-conditioned landscaped office buildings

Abstract: Noise measurements and a questionnaire survey were carried out in air-conditioned landscaped offices in the present study in an attempt to find out what existing noise index gives the best correlation with the auditory sensation feeling of office workers. Results from statistical analyses show that the Equivalent Sound Pressure LEvel is the best among the 14 commonly used noise indices for this purpose. It is also found that the less commonly used Zwicker's loudness level performs better than the commonly adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 17 publications
4
33
1
Order By: Relevance
“…The sound pressure levels of the background noises were analyzed in terms of A-weighted equivalent sound pressure levels (L Aeq ). The measured noise levels of the offices varied from 47.0 dBA to 62.4 dBA and this result is consistent with the previous study (Tang, 1997) reporting that background noise levels for five-minute of 26 open plan offices ranged between 45 dB and 70 dB. The noise levels of the offices in China were greater than the levels of the offices in Korea, and this is mainly because the noise levels from the air conditioning system in China were greater than those in Korea.…”
Section: Offices and Participantssupporting
confidence: 81%
“…The sound pressure levels of the background noises were analyzed in terms of A-weighted equivalent sound pressure levels (L Aeq ). The measured noise levels of the offices varied from 47.0 dBA to 62.4 dBA and this result is consistent with the previous study (Tang, 1997) reporting that background noise levels for five-minute of 26 open plan offices ranged between 45 dB and 70 dB. The noise levels of the offices in China were greater than the levels of the offices in Korea, and this is mainly because the noise levels from the air conditioning system in China were greater than those in Korea.…”
Section: Offices and Participantssupporting
confidence: 81%
“…Tang (1997) found that the less commonly used Zwicker's loudness level performs better than the commonly adopted NC curves (Beranek, 1989) when predicting the noise perceptions of office workers in air-conditioned landscaped offices. Berglund et al (2002) used Zwicker's loudness scale to investigate annoyance levels due to environmental noises.…”
Section: B Zwicker's Loudnessmentioning
confidence: 99%
“…3. A comparative cumulative frequency of the levels of LAeq at each 15-min interval over the daytime (9)(10)(11)(12)(13)(14)(15)(16)(17) and the nighttime (17)(18)(19)(20)(21)(22)(23)(24) in the 16 surveyed hospital lobbies.…”
Section: Noise Measurementsmentioning
confidence: 99%
“…22,23 The studies by Tang et al also found L Aeq to be generally well correlated with subjective auditory sensation, with other metrics performing well in certain circumstances. [18][19][20][21] Tang and Wang noted that many of their measured spectra contained some degree of tonality, but a detailed investigation of such was not the focus of their work. 21 Despite these previous studies generally supporting L Aeq , other studies have demonstrated limitations in the metric.…”
Section: Previous Researchmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Ayr et al examined the effectiveness of several criteria methodologies using questionnaires and in situ office a͒ Present address: Woodruff School of Mechanical Engineering, Georgia Institute of Technology, Atlanta, GA 30332-0405. Electronic mail: eryherd@hotmail.com noise measurements.…”
Section: Previous Researchmentioning
confidence: 99%